Evolution of value chain and governance actor responses to the plastic leakage problem in South Africa - Chitaka, Takunda Yeukai; de Kock, Lorren; von Blottnitz, Harro (Frontiers in Sustainability, 2022)
An estimated 15 000 – 40 000 tonnes of plastic waste leaks into the oceans from South Africa annually. This has put the management of plastic products in the spotlight. In South Africa, life cycle management (LCM) is not a term that is commonly used however some companies have adopted LCM tools and concepts including cleaner production, sustainable procurement and design for recycling. Interviews with key value chain actors were conducted in 2017 and 2018 – 2019, on the influence of plastic leakage on plastic product life cycle management. In 2017, actors largely did not view themselves as responsible for plastic leakage, mostly putting blame on consumers. During the second interview period, a shift was observed wherein the actors recognized the role of product design in plastic leakage and started taking a more active role in its mitigation from the perspective of extended producer responsibility. The drivers for addressing marine pollution mirrored those for the adoption of LCM tools, including maintaining a competitive advantage and meeting investor and consumer expectations. In 2020, the South African Plastic Pact was developed and launched, which aims to create a circular economy for plastic packaging. As of October 2021, the majority of interviewed value chain actors are members. Ultimately the increasing concern surrounding plastic pollution has directly influenced value chain actors’ perspectives and actions.